PERSIAPAN DAN KARAKTERISASI PALLADIUM BERBASIS ELEKTROLISIS UNTUK SEL BAHAN BAKAR - Chiou, Yuh Jing; Stefandra, Praisela Ivane; Dewi, Rini Kartika (jurnal ATMOSPHERE, 2024)
This research presents the results of research regarding the preparation and characterization of palladium (Pd)-based electrolytes for applications in fuel cells. In the context of utilizing efficient and environmentally friendly energy sources, Fuel Cells offer an innovative solution by converting chemical energy into electrical energy without a combustion process. This research aims to develop an electrolyte that has high performance, with a focus on analyzing the physical and chemical properties of the resulting electrolyte. The methods used include synthesis of a Pd-based electrolyte and characterization using advanced analytical techniques such as X-ray diffraction (XRD) and Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). The research results show that Pd-based electrolytes have better ionic conductivity and higher stability compared with conventional electrolytes. In addition, variations in operating conditions have a significant effect on fuel cell performance, with the finding that increasing the electrode surface area can effectively increase hydrogen production.